THE IMPLEMENTATION OF THE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) MODEL IN TEACHING ANALYZING THE STRUCTURE AND LANGUAGE OF DESCRIPTIVE TEXTS - Sopari, Sopari (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
This study aims to determine if the Cooperative Integrated Reading and Composition (CIRC) model is effective in teaching class VII students at SMP NU Kaplongan Indramayu about the structure and language of descriptive texts. The researchers chose the CIRC model because it is relevant and helpful in teaching students about descriptive texts. The study was conducted at NU Kaplongan Middle School, with a total of 204 students from 6 classes. The sample for the study included 34 students from class VII E and 34 students from class VII F. The data collected included initial and final tests from both the experimental and control classes. The results of the study are as follows. The t-value value for both research groups is 5.892, while the t-table value is 1.996. Therefore, the t-value is greater than the t-table value, indicating that the alternative hypothesis stating the significant influence of the CIRC learning model on the ability to study descriptive texts is accepted. Additionally, the CIRC learning model brings about significant changes in teaching methods and student learning. It promotes active, creative, effective, and enjoyable learning experiences. It also helps students develop problem-solving skills and encourages teamwork and mutual respect.